Communicative creativity and destructiveness - Kamenskaya, Tatyana G. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The author specifies characteristics of communicative technologies which emerge in contemporary world or derive from early traditional tricks into innovative forms of communicative cooperation. The use of explicative method has helped to update characteristics of some communicative patterns, and thus has demonstrated that while developing they do not only conduce to mutual understanding but are also exploited with negative and destructive consequences. It is claimed that current communicative destructiveness is carried out with the help of such technologies as intrigue, instigation, lies (concealing true intentions), fibs, faking, trolling. It has been defined that from the technologies mentioned above only instigation is written down in law and is subject to legal prosecution. Other acts of influence are difficult to convict and do not result in criminal or administrative penalty. The aggressive technologies created via internet are gradually debunked with the help of the same computer stuff. And only human based aggressive social communicative technologies of intrigue and lies are still difficult to reveal and penalize.